2010
DOI: 10.1128/mcb.00518-10
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Distribution of MacroH2A1 Histone Variants in Mouse Liver Chromatin

Abstract: Studies of macroH2A histone variants indicate that they have a role in regulating gene expression. To identify direct targets of the macroH2A1 variants, we produced a genome-wide map of the distribution of macroH2A1 nucleosomes in mouse liver chromatin using high-throughput DNA sequencing. Although macroH2A1 nucleosomes are widely distributed across the genome, their local concentration varies over a range of 100-fold or more. The transcribed regions of most active genes are depleted of macroH2A1, often in sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 40 publications
6
71
1
Order By: Relevance
“…These results reinforce our previous finding that macroH2A.1 has a role in regulating metabolism-related genes, especially genes related to lipid metabolism (23,24). Two of the other 5 new genes also have a clear connection to lipid metabolism: Lepr (1.9-fold increase) encodes the receptor for leptin, an adipokine that has a central role in energy homeostasis (37), and Rgs16 (2.3-fold increase) encodes a GTPase-activating protein that can regulate fatty acid and glucose metabolism in the liver (38).…”
Section: Knockout Of Macroh2a2supporting
confidence: 82%
See 3 more Smart Citations
“…These results reinforce our previous finding that macroH2A.1 has a role in regulating metabolism-related genes, especially genes related to lipid metabolism (23,24). Two of the other 5 new genes also have a clear connection to lipid metabolism: Lepr (1.9-fold increase) encodes the receptor for leptin, an adipokine that has a central role in energy homeostasis (37), and Rgs16 (2.3-fold increase) encodes a GTPase-activating protein that can regulate fatty acid and glucose metabolism in the liver (38).…”
Section: Knockout Of Macroh2a2supporting
confidence: 82%
“…Our previous study of macroH2A.1 distribution in adult liver found that macroH2A.1 is typically organized in relatively large domains that can be enriched, neutral, or depleted for macroH2A.1 nucleosomes. The transcribed regions of most active genes were strongly depleted of macroH2A.1, while inactive genes showed no strong bias toward depletion or enrichment (24). Our new fetal liver macroH2A.1 map appears consistent with these findings, showing domains of enrichment, neutral domains, and discrete domains of depletion that correspond to genes (Fig.…”
Section: Knockout Of Macroh2a2supporting
confidence: 75%
See 2 more Smart Citations
“…Subsequently, this has been well established in vitro and in vivo by a large body of evidence (reviewed in [15,18]). In mouse liver chromatin, for instance, macroH2A1 was found to be depleted from the transcribed regions of most active genes [39,40]. Two other genome-wide studies later confirmed in other cell types that macroH2A occupancy had a general negative correlation with transcriptional future science group activity [28,41].…”
Section: Is Macroh2a Also a Gene 'Activator'?mentioning
confidence: 83%